BAHASA AKUNTANSI SEBAGAI âDISCOURSE-DRIVENâ DALAM BUDAYA KAPITALISME BARU - Witono, Banu (Riset Akuntansi dan Keuangan Indonesia, 2016)
It is undeniable that accounting as a science or practice developed at this time considered to be born of the "womb" of capitalism, also led to the development of accounting theory is consistent with capitalism itself. This article highlights the dialectic accounting laden with cultural values contained therein. A study of discourse is used to generate an understanding of how the language has become a discourse-driven to the new capitalism in order to generate the values in a culture where accounting flourish. The basic concepts and theories developed in accounting has become a tool of technology which is used as a justification of the interests in favor of the neo-capitalist. Keywords: Accounting Language, Discourse-Driven, Neo-capitalism